Heating Up the Market: A case study on KAISO Hot Pepper Sauce - Wu, Shuang; Smith, Connor; Rolf, Randy (MacEwan University Student eJournal, 2023)
The study was conducted for a locally based company that wished to expand their consumer base and market reach. The relationship between consumer attitudes and brand perception was examined to identify potential marketing approaches. Results were gathered through a questionnaire (n= 136), in order to model consumer profiles and analyze their affect on product perception. The resulting multivariate regression model indicated that the difference in receptiveness to Kaiso’s branding between the Black/African demographic and the Caucasian demographic was significant. The average Black/African participant perceived the product more negatively than the average Caucasian participant. The same observation applied to South Asian demographics. Consumers’ self-reported likelihood to purchase was positively correlated with an increase in consumption rate across all participant profiles. Notably, aspects that provide opportunities to improve in the peer sauce industry are associated with traditional spicy cuisine, which is a trait correlated with the desire for perceived authenticity over other product attributes.